Teknik Visualisasi terhadap Tingkat Stres Pasien Diabetes Mellitus - I Nengah Sumirta; I Wayan Candra; I Dewa Made Ruspawan (Jurnal Gema Keperawatan, 2017)
The purpose of this study is to find the influence of technique visulisasi on the level of stress patients diabetes mellitus.Use design experiment specious (quasi experiment design to a draft non randomized controle group pre test-post test design). Large sample 37 people where 20 people given mistreatment and 17 people as control. Sample is the patient DM outpatient at puskesmas kuta north meet kriteria inclusion and exclusion. The changes measured is the stress in patients DM before and after treatment technique given: visualization Analysis data using dependent t test. The results of the study in the treat show the before treatment stress low level 3 people (15%), and 12 people ((60%) and high five people (25%). After treatment low five people (29 %), was 9 people (53 %) and high 3 people (18%).In the control group: the levels stress before the treatment is a low level 5 people (29,41%), was 8 people (47,06 %), and high 4 people (23,53%) and after treatment stress low level 5 people (29,41%) , was 9 people (52,94%), and a height of 3 people (23,53%).The results of t count = 7,877 with a significance p = 0.05 is 0,000. It showed there was influence significant the technique visualize on the level of stress patients diabetes mellitus.